The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27351
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Engineering Design in an Academic Makerspace: Blending Theory and Practice to Solve Client-based Problems

Abstract: The proliferation of higher education makerspaces -sites where students, faculty, and staff design and build solutions to engineering challenges and other problems -suggests that such spaces have a special value on university campuses in a number of contexts. This paper reports on the unique impact of a higher education makerspace (the Yale Center for Engineering Innovation and Design) in the arena of design education. We review the history of design education, identifying the values of this form of pedagogy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…By fostering creativity and an awareness of the importance of trial and error, programs that incorporate makerspace education have shown a significant increase in student participation [9,14]. Courses taught in higher-education makerspaces meet long-standing design education goals [15,16].…”
Section: What Is a Makerspace?mentioning
confidence: 99%
“…By fostering creativity and an awareness of the importance of trial and error, programs that incorporate makerspace education have shown a significant increase in student participation [9,14]. Courses taught in higher-education makerspaces meet long-standing design education goals [15,16].…”
Section: What Is a Makerspace?mentioning
confidence: 99%
“…There are five current VIP courses, with a new course this semester taking full advantage of the makerspace for meeting, prototyping, and equipment. Future plans include merging some of the best practices of the Yale CEID model for design courses (Wilczynski, 2016) with more student-based and informal learnings models like the Innovation Studio at Georgia Tech (Forest, 2014) or the d-school at Stanford to create an environment that can best support engineering design education. This blended model will work best as it acknowledges the institutional constraints of new curriculum design and implementation while also providing more opportunities for experimentation and interdisciplinary collaborations across departments in the engineering school and across different schools within the university.…”
Section: Future Work: Experiments To Develop the Community Of Practicementioning
confidence: 99%
“…While makerspaces, hackerspaces, innovation labs, fab labs, and engineering labs are technically defined with different meanings, in general usage, those terms are considered to be interchangeable [2]. In general, makerspaces are credited with helping to increase diversity and inclusion in the STEM fields.…”
Section: Best Practices Noted At Universities and Public Librariesmentioning
confidence: 99%
“…But, if the makerspace activities are interesting to a larger population, that may be enough to encourage the potentially diverse, non-engineering population to get involved at the makerspace. Encouraging interdisciplinary activities not only increases usage of the makerspace [4], especially with Entrepreneurial majors, but also increases the diversity of those who use the lab space [3] [4] and their overall interaction [2].…”
Section: Best Practices Noted At Universities and Public Librariesmentioning
confidence: 99%
See 1 more Smart Citation